Conservation history hung on a thread: the unlikely chain of events deciding New Zealand's importation of stoats and weasels, 1880–1892. Issue 3 (3rd July 2022) - King, Carolyn
ABSTRACT: The history of the introduction of stoats ( Mustela erminea ) and weasels ( M. nivalis ) to New Zealand is a paradigm example of how the course of history can turn on a sequence of simple, unconnected events. When Victorian pastoralists were faced with the dilemma that rabbits ( Oryctolagus cuniculus ) were thriving better than their sheep, they sought to enlist the rabbits' natural enemies to save them from crippling economic losses. An improbable series of circumstances linked four principal characters whose dramatic anti-rabbit policies seemed reasonable to them but have had catastrophic consequences. A Lincolnshire farmer, Samuel Grant, visiting New Zealand in 1880, met Francis Rich, a pastoralist suffering rabbit damage; Rich and Grant organised a trial shipment of stoats and weasels escorted by Lincolnshire trapper Walter Allbones in 1883. Supervising Rabbit Inspector Benjamin Bayly authorised thousands more over 1884–1889, until imports stopped in 1892. This paper describes why only the four principal players could have made each necessary link in the chain, and how easily it could have been broken. Legal attempts to stop the importations failed in 1876, but within another 25 years, the 'natural enemies' policy was recognised as a tragic mistake, and its proponents were widely discredited.